Efficacy and safety of bronchoscopic lung volume reduction for chronic obstructive pulmonary disease: a systematic review and network meta-analysis - Zhang, Ranran; Zheng, Ziwen; Bian, Yiding; Deng, Mingming; Herth, Felix; Hou, Gang (Expert review of respiratory medicine, 2024)
Various bronchoscopic lung volume reduction (BLVR) methods have been developed to treat chronic obstructive pulmonary disease (COPD). The efficacy and safety of these interventions remain unclear. This study assessed the efficacy and safety of various BLVR interventions in COPD patients. PubMed and Embase were searched from inception to 21 October 2023. The primary outcomes assessed included the 6-min walking distance (6MWD), St. George Respiratory Questionnaire (SGRQ) score, lung function, and adverse events (AE). A frequentist approach with a random-effects model was used for a network meta-analysis. Twelve randomized controlled trials (RCTs) with 1646 patients were included in this meta-analysis. Patients treated with an endobronchial valve (EBV) achieved a minimum clinically important difference (MCID) in 6MWD and SGRQ at 6 months. Patients treated with coils achieved MCID in the SGRQ score at 12 months. Patients with aspiration valve system and bronchoscopic thermal vapor ablation (BTVA) achieved MCID in the SGRQ score at 6 months. In COPD patients, EBV should be considered first, while being wary of pneumothorax. Coil and BTVA are potential therapeutic alternatives. Although BTVA demonstrates a safer procedural profile than coils, additional studies are imperative to clarify its efficacy.
Online veröffentlicht: 08. August 2024
Gesehen am 23.07.2025